A proposal of texts for political ideological work and the value formation of the future physical culture professional - Ana Isel Rodríguez-Cruz; Noelia Afre-Socorro; Ana Delia Martínez-Bravo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2013)
The values like complex formations of the personality are very related to the person's own existence and they have a lot to do with each individual's ideological political formation, that's why, by means of a texts selection associated to this theme and from the Communicative Spanish subject, the authors propose to deep in the ideological political work and the main values in correspondence with the expectations, interests and the necessities of the current Cuban society. After the application of theoretical, empirical and statistical methods the necessity of reinforcing the ideological political work and the formation of values in our students was verified. In this way, the subject team puts in practice the educational ways and the performance ways by the teacher, in such way from the classes, the teacher generates changes in the students and contributes to the professional's formation that demands the modern society. For this reason, the teacher works with texts through diverse themes related like history, sport, personalities, and important events. (The texts make emphasis in the fight that at present is taken place for the free of the Cuban five), among others. The texts analysis includes the search of key words, the relationships among significant and meaning, the translation, interpretation and extrapolation of the same ones, the paragraph qualities, as well as the rhetorical patterns or methods of development of it, among other aspects. All of these items contribute to reinforce the values that the students have and at the same time the teacher's work facilitates the students express their feelings and thinking in correspondence with their personality.